2014
DOI: 10.3103/s036152191404003x
|View full text |Cite
|
Sign up to set email alerts
|

Production of fuel briquettes from anthracite fines

Abstract: Experimental data on the development of a technology for the production of fuel briquettes from anthracite fines, slack coal, and coal slurries available in the Rostov oblast are presented. The effects of the moisture content and particle size distribution of the coal components, the moisture content of the charge, the composition of a binder, the compacting pressure, and the regime of hardening on the technical proper ties of the fuel pellets were studied. The possibility of obtaining water resistant briquett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Afşin‐Elbistan lignite sample and the rice husk sample were briquetted under four different pressures without any binder material to determine optimum briquetting pressure. Several researches indicated that an optimum briquetting pressure should be selected to obtain fuel briquettes with adequate mechanical strength . The effects of the briquetting pressure on the shatter index, compressive strength, and water resistance of the produced briquettes are graphically displayed in Figures and .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afşin‐Elbistan lignite sample and the rice husk sample were briquetted under four different pressures without any binder material to determine optimum briquetting pressure. Several researches indicated that an optimum briquetting pressure should be selected to obtain fuel briquettes with adequate mechanical strength . The effects of the briquetting pressure on the shatter index, compressive strength, and water resistance of the produced briquettes are graphically displayed in Figures and .…”
Section: Resultsmentioning
confidence: 99%
“…Using molasses as binder material (12 wt %) at a briquetting pressure of 200 MPa gave stronger briquettes with shatter index of 2572 and compressive strength of 12.2 MPa. Buravchuk and Guryanova used molasses as the base component of a binding agent to produce fuel briquettes from anthracite fines and reported that the produced briquettes satisfy consumer requirements in terms of drop, abrasion, and compression strengths.…”
Section: Resultsmentioning
confidence: 99%